On my way! : a volunteer firefighter/EMT's story - McCann, Dan ([Publisher not identified], 2024)
"There are over a million firefighters in the United States. Over 650,000 of them are volunteers. This book is based on the experiences of one of those volunteers, Lieutenant Dan McCann. Lt. Dan is a 68-year-old retired university professor who has been fighting fires and responding to emergency medical calls in Eastern Washington State for over 27 years. In this book he describes emergencies he and his fellow volunteers have responded to in their ongoing efforts to help members of their rural community survive the worst day of their lives." -- Back cover